The Influence Of Organizational Innovative Climate, Knowledge Sharing And Work Engagement On Innovative Behavior Among Engineers In Electrical And Electronic Mncs In Malaysia - Mohamad, Wan Maisara Wan (2019)
The importance of innovative behavior among engineers currently is vital and competition based on innovation can serve as a basis for sustainable development, especially for multinational companies in Electrical and Electronic sector in Malaysia. Grounded by the social cognitive theory, this study utilized a research model examining organization innovative climate factors (support for innovation, competitiveness, and performance orientation), individual factors (altruism, knowledge self-efficacy, reciprocity, reputation, and trust), and ICT use as predictors of innovative behavior with knowledge sharing (knowledge giving and knowledge receiving) as mediating variables. In addition, work engagement (vigor, dedication, and absorption) as moderator to strengthen relationship between knowledge sharing (knowledge giving and knowledge receiving) and innovative behavior.